KEMATANGAN KARIR SISWA SEKOLAH MENENGAH KEJURUAN DARI PERSPEKTIF GENDER DAN PERILAKU DIGITAL - Arismen, - (2022)
Career uncertainty and unpreparedness of vocational students in facing the world of work are influenced by their knowledge of the field of work. Information about these fields indicates the level in development of students' career maturity during their education process. In addition, the current COVID-19 pandemic condition has forced more student activities in the digital world, thus affecting the construction of their knowledge. This causes changes in the behavior of access to information which is more dominated in the digital world. This study discusses how the development of career maturity of vocational high school students from the perspective of gender and students' digital behavior. The research method used is a descriptive correlational quantitative approach using the instrument Career Maturity Inventory (CMI) of career maturity theory by Donald E Super. A total of 335 students (230 boys and 105 girls) in class XII in Public and Private Vocational Schools in Kampar Regency, Riau Province participated as respondents in this study. The research findings show that students' digital behavior in exploring career information on the internet is in the moderate category where their ability to analyze career information they get in digital media has not been well developed. Meanwhile, the level of career maturity of students is in the high category but there is no significant difference in career maturity between male and female students. Another finding in this study shows that students' digital behavior has a linear relationship with the development of their career maturity with a correlation coefficient of 35.3%.